Implementasi Kebijakan Pemilihan Kepala Daerah Dengan Sistem Noken di Papua - Soponyono, Soponyono (JURNAL EKOLOGI BIROKRASI, 2022)
Direct Regional Head Election or Pilkada is an interesting development in the history of politics in Indonesia. Pilkada is the initial momentum of people's sovereignty and the political system and democracy at the regional level. This phenomenon shows the great enthusiasm of the community in appreciating the Pilkada process directly and this can be interpreted as the operationalization of community autonomy to determine their own and direct regional heads. One of the real phenomena that occurs is the use of the noken system in regional head elections in Papua. The method used is descriptive research with a qualitative approach. The implementation slot deposit 5000 of policies with the Noken system is still marked by various inequalities that require professionalism of election organizers, but if democracy with the Noken system turns out to be running better and packaged attractively, it will be positive. It is fitting that the implementation of this noken system policy is really implemented with a professional objective by the Government, KPU, Bawaslu, it is not impossible that conflicts in regional head elections with this system can be avoided. Much needs to be addressed, including the neutral role of stakeholders in providing information about representation in elections with the noken system, good rules of the game according to the provisions, monitoring the operation of the noken system which leads to accommodation of local wisdom to become a cultural solution in a modern democratic system.